The Synergetic Economic Evaluation of PSC Cost Recovery and Gross Split Schemes on Field A - Prayang Sunny Yulia; Adji Nadzif Sidqi; Syamsul Irham; Mustamina Maulani; Puri Wijayanti (Journal of Earth Energy Engineering, 2023)
In month of August, year 2021, there was an alteration in the production-sharing contract for this field. The contract previously used was Production Sharing Contract (PSC) Cost Recovery, which changed to PSC Gross Split. This contract comparison aims to synergetically evaluate the comparison of the two economic models and also to determine a more efficient and appropriate scheme to be applied to field A, as well as to analyze the parameters that can affect the economic indicators of field A. The results of the economic analysis that has been carried out show that the PSC Gross Split scheme is better than the PSC Cost Recovery scheme. For PSC Cost Recovery, the Net Present Value (NPV) obtained for 30 wells is equal to 13,848,000 US$, the average Interest Rate of Return (IRR) is 118%, the average Pay Out Time (POT) is 1.43 years, the Contractor Take is 20,740,000 US$, and the Government Take is 176,587,000 US$. Whereas for PSC Gross Split, the NPV obtained for 30 wells was US$ 37,906,000, the average IRR was 245%, the average POT was 1.30 years, the Contractor Take was US$ 52,544,000, and the Government Take was 136,402,000 US$. The sensitivity analysis that has been carried out shows that the parameters of the amount of oil production and the price of oil have a significant effect on both schemes.